2008
DOI: 10.1213/ane.0b013e31816069d9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Lumbar Interspinous Spaces: Palpation Versus Ultrasound

Abstract: There was poor agreement between palpation and ultrasound estimation of the specific lumbar interspace, and when there was disagreement, the ultrasound estimate was more often higher than the palpitation estimate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(62 citation statements)
references
References 15 publications
3
58
0
1
Order By: Relevance
“…2 Moreover, for the lumbar vertebral region, it has been shown that clinicians are more likely to select interspaces that are one or two spaces higher than the correct space. 2,20 When trying to identify the T7-8 interspace in our study, the surface landmark method was more likely to indicate a more caudal interspace than ultrasonography. When using chest radiography as a gold standard for the thoracic spine, the inaccuracy has been to identify lower interspaces.…”
Section: Discussionmentioning
confidence: 81%
“…2 Moreover, for the lumbar vertebral region, it has been shown that clinicians are more likely to select interspaces that are one or two spaces higher than the correct space. 2,20 When trying to identify the T7-8 interspace in our study, the surface landmark method was more likely to indicate a more caudal interspace than ultrasonography. When using chest radiography as a gold standard for the thoracic spine, the inaccuracy has been to identify lower interspaces.…”
Section: Discussionmentioning
confidence: 81%
“…This localization process may be problematic when patients are obese, pregnant, or have spinal abnormalities, including misalignment or degenerative changes [3][4][5][6][7]. Ultrasound can be used to gain a more accurate understanding of a patient's spinal anatomy, leading to fewer needle insertion attempts and spinal needle manipulations, and improve patient satisfaction [3,5,6,[8][9][10][11][12][13][14][15][16][17][18]. Further, a decrease in the number of needle insertion attempts has been shown to correlate with a decreased incidence of postdural puncture headache [19], new-onset persistent low-back pain [20], and puncture site bleeding [21].…”
Section: Introductionmentioning
confidence: 99%
“…These studies have reported a strong relationship between the epidural space depth measured by US and the insertion depth of the needle, confirmed more recently by other authors [6,7]. US can also help to identify the interspinous spaces where palpation has been shown to be frequently inaccurate [8]. Pre-procedure US scanning of the lumbar spine is currently widely used to help perform epidural anesthesia or lumbar puncture [9][10][11].…”
Section: Introductionmentioning
confidence: 72%
“…However, in patients with easily palpable anatomical landmarks, the use of pre-procedural spinal ultrasound did not improve the ease of insertion of labour epidural catheters as compared with the traditional palpation technique [28]. Finally, in 120 orthopedic patients undergoing lower limb surgery, US was associated with both a significantly higher number of successful epidural puncture on the first needle insertion attempt (65% vs. 32%) and a significantly smaller number of needle passes (6 [1][2][3][4][5][6][7][8][9][10] vs. 13 [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]) [19]. In our study, number of redirections and number of injections performed in a single attempt were not different between the two groups, which probably explain why we did not find any difference in VAS pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation